Increasing the functionalities and accuracy of fisheries electronic monitoring systems. Issue 6 (10th May 2019) - Gilman, Eric; Legorburu, Gonzalo; Fedoruk, Andrew; Heberer, Craig; Zimring, Mark; Barkai, Amos
Abstract: Fisheries‐dependent data underpin essential scientific and management applications. Electronic monitoring (EM) systems are increasingly being used to supplement human observer programmes and provide coverage where none previously existed. Candidate methods were identified to expand EM functionalities to collect data fields of human observer programmes that contemporary EM systems either cannot collect or require improved accuracy. Options were also identified to enable EM systems to collect new data fields that human observers cannot collect, prioritized by scientists, managers and the catch sector. Many EM limitations could be resolved through simple changes of repositioning existing or adding new cameras with suitable fields of view and resolution, integrating additional sensors, and making minor modifications to fishers' practices. Research, development and trials, however, are required for possible EM integration of some existing and emerging technologies. Whether an EM improvement method should be pursued requires consideration of: the relative importance for meeting monitoring objectives; the accuracy and cost of alternative monitoring methods, such as data collection by fishers with EM auditing, and by dockside inspections; impacts on fishing operations and crew safety; and net costs. Active support from fishers is necessary for EM collection of some data fields, where EM enables auditing fisher compliance with required procedures. Having EM systems supply data desired by the seafood industry could augment their support for EM and incentivize fisher cooperation. EM systems have the capacity to collect most data fields collected by human observer programmes with high precision and in some cases improved accuracy, to supply information of interest to seafood companies, and to meet expanding data requirements as fisheries management frameworks continue to transition to implementing elements of ecosystem‐based fisheries management.